2000
DOI: 10.1097/00007890-200004270-00030
|View full text |Cite
|
Sign up to set email alerts
|

A COMPARISON OF FETAL AND ADULT PORCINE ISLETS WITH REGARD TO Gal?? (1,3)Gal EXPRESSION AND THE ROLE OF HUMAN IMMUNOGLOBULINS AND COMPLEMENT IN ISLET CELL CYTOTOXICITY1

Abstract: Gal alpha(1,3)Gal expression is occasionally detectable on adult porcine islet cells, but not as readily and at a lower level, compared with fetal islet cells. Thus, as porcine fetal islets mature to adult islets, the expression of the Gal alpha(1,3)Gal epitope gradually diminishes. Consequently, cytotoxic anti-Gal alpha(1,3)Gal antibodies in human serum play an important role in the lysis of fetal but not adult porcine islet cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 19 publications
1
39
0
Order By: Relevance
“…The rationale for this was that expression of ␣-galactosyl epitopes on neonatal porcine islet cells has previously been shown (23). No staining of any of these islet endocrine cells with BS-1 was detected, which is consistent with the findings that these epitopes are not expressed in adult pig (24) or adult mouse (22) pancreatic tissue.…”
Section: Discussionsupporting
confidence: 81%
“…The rationale for this was that expression of ␣-galactosyl epitopes on neonatal porcine islet cells has previously been shown (23). No staining of any of these islet endocrine cells with BS-1 was detected, which is consistent with the findings that these epitopes are not expressed in adult pig (24) or adult mouse (22) pancreatic tissue.…”
Section: Discussionsupporting
confidence: 81%
“…Early studies suggested abundant expression of a-Gal on porcine fetal endocrine cells (2); a finding that was debated because of the lack of sensitivity and specificity of the Griffonia simplicifolia IB 4 (4,5), whereas the expression of a-Gal in adult porcine islets is less consistent and appears to be confined to nonendocrine cells (4,5). Still, the role of a-Gal/anti-Gal in pig islet xenograft rejection is controversial, and it has been suggested that although pig islet xenografts are susceptible to antibody-mediated rejection in a1,3-galactosyltransferase (a1,3Gal-T) knockout mice, rejection could not be triggered by anti-Gal and complement (6).…”
Section: Antibodies (Abs) Specific For Carbohydrates Are a Major Concmentioning
confidence: 99%
“…Each of these sources is associated with distinct advantages and disadvantages in terms of biocompatibility in foreign systems. Sources assert that FP ICCs and NPCCs express the porcine "Gal" epitope, an immunogenic carbohydrate chain incompatible with transplantation in humans, to a greater extent than adult porcine islets [ 43 ]. Should a fragment of a transplanted islet be incompletely encapsulated and protruding into the "extracapsular" environment, preformed human anti-Gal IgM and IgG antibodies immediately recognize this epitope, trigger the complement cascade, and compromise porcine islet survival [ 44 ].…”
Section: +mentioning
confidence: 99%
“…Therefore, they are economically ineffi cient to harvest, isolate and culture compared to FP ICCs and neonatal islets. Like neonatal islets, adult porcine islets express gal alpha [1,3] gal antigens, albeit to a signifi cantly lesser extent [ 43 ]. Consequently, anti-gal antibodies present in human sera are responsible for the lysis of exposed neonatal islet cells, but have a diminished role in the eradication of incompletely encapsulated adult islets [ 74 ].…”
Section: Fetal Porcine Islet-like Cell Clustersmentioning
confidence: 99%